In Vivo Propagation of Potato (Solanum Tuberosum L.) Cultivars - Khan , Farhat Ali; Irum, Shabana; Erum , Shazia; Muhammad , Aish; Nouroz , Faisal; Kanwal , Saima (Asian Journal of Agriculture and Rural Development, 2017)
In order to evaluate the morphological and qualitative characteristics of potato tubers total 35 genotypes were selected for propagation and trait screening. Consequential differences and diverse characteristics were found in all the genotypes after cultivation, wherein, among all the traits zina red, CIP 07, CIP 12, CIP 22, gave the highest results regarding yield and quality of potato tubers except CIP 03 which has low germination percentage and significant quality characters. The dendrogram was prepared to show the massive variation between potato genotypes. This screening is supportive to the permanent efforts to select the best genotype for the developing processing industry of Pakistan.